Stations in Politics are Unjustness in the era of the Prophet Muhammad, Peace and Blessings be Upon him - Abdul Qahar , Wehbeh (Islamic Sciences Journal, 2023)
ABSTRACT The basis of each country is its economy. In view of this, the Prophet (peace and blessings be upon him) developed a strategy and identified the weak point of the enemy and thus worked to demolish the infrastructure of the Quraish economy so he sent patrols and companies on the path of their trade and the goal of sending military patrols is to inform them that their main trade is in danger and manifestation of the side of the power of Muslims and the introduction of terror into their hearts, just as any country that wants prosperity maintains its economy and tries to contain all its members. When looking at the position of the Quraysh in that matter, we see that they were exchanging money by involving the owners of small sums with them and thus the prosperity of Mecca on the economic side while the system was aristocration. Although the West had drawn up international humanitarian law and the 1949 Geneva Convention the laws for protecting noncombatants are somewhat similar to what Islam has enacted.